Novel method for the fabrication of ultrathin, free-standing and porous polymer membranes for retinal tissue engineering. Issue 28 (5th July 2017) - Tan, Edgar Yong Sheng; Agarwala, Shweta; Yap, Yee Ling; Tan, Colin Siang Hui; Laude, Augustinus; Yeong, Wai Yee
Abstract : Retinal degeneration causes permanent visual loss and affects millions of people worldwide. Abstract : Retinal degeneration causes permanent visual loss and affects millions of people worldwide. Cell transplantation may have the potential for retinal regeneration. However, several problems hinder the successful repair of the retina including cell delivery, integration, and survival. Recent studies have shown that the use of scaffolds can address these obstacles. Synthetic scaffolds are being explored to mimic the functions of Bruch's membrane, an extracellular matrix that acts as a molecular sieve, to maintain the metabolic exchange between the vasculature and outer retina. This work aims at fabricating an ultrathin and porous membrane, which mimics Bruch's membrane, using a novel method. We have developed a fast, easy and single-step method to create a free-standing, porous and ultrathin PCL membrane, through dropcasting of a polymer blend on a liquid interface. The free-standing scaffold with nanometer pores is investigated for human retinal pigment epithelial (RPE) cell response. The results demonstrate that the synthesised membrane can act as a potential prosthetic Bruch's membrane for RPE transplantation.